Tools for innovation - Markman, Arthur B.; Wood, Kristin L. (New York ; Oxford : Oxford University Press, 2009)
This unique and exciting collaboration explores the practical methods that support innovation and creative design, from different ways of thinking and conceptualizing to computer-based tools. The authors present research on processes as well as on the evaluation of existing methods.
Description based on print version record.
Includes index.
Keywords: Creative thinking; Industrial design; Creative ability; Cognitive science -- Research